2019
DOI: 10.1186/s40463-019-0396-x
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the effectiveness of adjuvant radiotherapy in addition to surgery versus surgery alone at improving oncologic outcomes for early stage buccal carcinoma: A systematic review

Abstract: ObjectiveTo systematically review the evidence to evaluate oncologic outcomes for patients with early stage buccal squamous cell carcinoma treated with surgery versus surgery and adjuvant radiation therapy.Data sourcesOvid MedLine, EMBASE, Google Scholar, PubMed.Review methodsThe primary purpose was to perform a systematic review to determine the published literature comparing oncologic outcomes of patients with early stage (Stages I&II) buccal mucosal squamous cell carcinoma, treated with surgical resection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…2,3 Buccal SCC is characterized by aggressive locoregional behavior. 4 Previous studies have shown that buccal SCCs should be treated with surgery, 5 with adjuvant radiotherapy reserved for patients with advanced or more aggressive disease. 6 Patient age, tumor stage, and nodal status have been reported as significant prognosticators in buccal SCC.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Buccal SCC is characterized by aggressive locoregional behavior. 4 Previous studies have shown that buccal SCCs should be treated with surgery, 5 with adjuvant radiotherapy reserved for patients with advanced or more aggressive disease. 6 Patient age, tumor stage, and nodal status have been reported as significant prognosticators in buccal SCC.…”
Section: Introductionmentioning
confidence: 99%